Endoscopic transpapillary drainage for walled-off pancreatic necrosis with complete main pancreatic duct disruption by metallic stent placement: A retrospective study - Meng, Yajie; Ding, Jiewen; Tian, Chuan; Wang, Min; Tang, Kejiang (Frontiers in Medicine, 2022)
Background Walled-off pancreatic necrosis (WOPN) is a serious complication of acute necrotizing pancreatitis (ANP) and may lead to disruption of the main pancreatic duct (MPD). Endoscopic passive transpapillary drainage (PTD) is an effective method of treating MPD disruptions. However, WOPN with complete MPD disruption is usually accompanied by disconnected pancreatic duct syndrome (DPDS), especially with infected necrosis. Endoscopic PTD with a fully covered self-expanding metallic stent (FCSEMS) and plastic stent may be provided a reference for future applications for complete MPD disruption in patients with WOPN. METHODS Thee patients with WOPN caused by ANP were classified according to the 2012 Atlanta classification and definition. In all patients, ERCP was performed 2 times. First, 3 patients were diagnosed with complete MPD disruption by ERCP. At the time of diagnosis, a plastic pancreatic stent (7Fr) was placed. They underwent endoscopic PTD for WOPN with complete MPD disruption in which FCSEMS and plastic stents were the only access routes to the necrotic cavity. RESULTS The etiology of pancreatitis is the biliary origin, lipogenic and alcoholic. The WOPN size is from 6.5 to 10.2cm. The types of WOPN were two cases of mixed necrosis and one case of central necrosis. The three patients’ MPD disruption types were all complete. The locations of disruption were pancreatic body, head. The time from occurrence to the first ERCP was 18 days, 23 days and 26 days. The main symptoms were abdominal pain, abdominal distention, fever, gastrointestinal obstruction and or weight loss. Three patients with symptomatic WOPN and main pancreatic duct disruption underwent endoscopic transpapillary drainage with FCSEMSs and pancreatic plastic stents. Technical therapeutic success was achieved in 3/3 patients. The mean time of stenting was 28-93 days. The clinical symptoms connected with WOPN and collection disappeared postoperatively in all three patients. During the follow-up period of 4-18 months, no patients developed recurrence of the collection or other complications, such as gastrointestinal bleeding or reinfection. And their recoveries were uneventful. CONCLUSION In patients with WOPN with complete main pancreatic duct disruption, endoscopic transpapillary drainage with FCSEMSs and plastic stents may be an effective and safe method of treatment.